MCITP administrator : (Wiley Pub., 2007)
Covering Microsoft’s brand-new SQL 2005 administrator exam, this study guide walks you through setting up, maintaining, and troubleshooting database solutions. You’ll review key topics such as defining high-availability solutions, automating administrative tasks, defining security solutions, monitoring and troubleshooting the database server, and designing and executing deployments. Plus, the CD-ROM features leading exam prep software with an assessment test, test engine of case study practice questions, and electronic flashcards.